Comparison Of Skin Hydration Levels Given Watermelon (Citrullus Lanatus) Fruit Extract Moisturizing Cream With Moisturizing Cream Supplemented With Saccharide Isomerates On Dry Skin Of Female Wistar Rats (Rattus Norvegicus) - Dinda Yuliasari; Yensuari Yensuari; Rahmad Isnanta (International Journal of Health and Pharmaceutical (IJHP), 2023)
Starting early to care for your skin can prevent premature aging. Since the skin is the body's outermost organ, The skin protects interior organs from pollution, UV radiation, and diseasecausing microbes. Research is needed to confirm and maximize topical plant treatment and skin health medication benefits. This study employs an experimental approach, testing the effects of a moisturizing cream formulated with either watermelon (Citrullus lanatus) extract or a control group of saccharide isomerates on the skin of 25 rats (Rattus norvegicus). The research results show watermelon extract can be used as a medicine since it contains antioxidants and moisturizes the skin. A higher dose of watermelon extract and saccharide isomerate includes more chemical components that hydrate skin. 30% watermelon extract cream with 5% saccharide isomerate improved dry skin more after UVB exposure.